Bajo las palmas reales : una infancia cubana - Ada, Alma Flor. (Miami, Fla. : Alfaguara, 2000)
The author recalls her life and impressions growing up in Cuba.
Translation of: Under the royal palms.
Keywords: Ada, Alma Flor -- Childhood and youth; Authors, American -- 20th century -- Biography; Authors, Cuban -- 20th century -- Biography; Cuban American women -- Biography; Spanish language materials; Cuba -- Social life and customs; Autobiographies